2015
DOI: 10.1108/scm-08-2015-0331
|View full text |Cite
|
Sign up to set email alerts
|

Why supply chain collaboration fails: the socio-structural view of resistance to relational strategies

Abstract: Purpose – The purpose of this study is to elaborate theory regarding the reasons why collaboration strategies fail. The relational view posits that supply chain integration can be a source of competitive advantage. Few firms, however, successfully co-create value to attain supernormal relational rents. Design/methodology/approach – This study uses a quasi-longitudinal, multi-case interview methodology to explore the reasons why collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(211 citation statements)
references
References 86 publications
6
191
0
1
Order By: Relevance
“…Prior research has identified SCC in various ways, with common sentiments focusing on the relationship (Vereecke and Muylle, 2006;Cao and Zhang, 2011), the process (Simatupang and Sridharan, 2008;Fawcett et al, 2008, Cao andZhang, 2011), and gaining mutual benefits from collaborating with SC partners (Fawcett et al, 2015;Soosay and Hyland, 2015). SCC aims at mutual benefits and profit maximisation for the involved SC members through a well-coordinated planning and delivery of offerings (Simatupang and Sridharan, 2008;Cao and Zhang, 2011).…”
Section: Supply Chain Collaboration and Its Elementsmentioning
confidence: 99%
“…Prior research has identified SCC in various ways, with common sentiments focusing on the relationship (Vereecke and Muylle, 2006;Cao and Zhang, 2011), the process (Simatupang and Sridharan, 2008;Fawcett et al, 2008, Cao andZhang, 2011), and gaining mutual benefits from collaborating with SC partners (Fawcett et al, 2015;Soosay and Hyland, 2015). SCC aims at mutual benefits and profit maximisation for the involved SC members through a well-coordinated planning and delivery of offerings (Simatupang and Sridharan, 2008;Cao and Zhang, 2011).…”
Section: Supply Chain Collaboration and Its Elementsmentioning
confidence: 99%
“…Very little guidance is provided on how supply chain members could collaborate on joint sustainability initiatives, and green supply chain collaboration has remained challenging. With no proper governance mechanisms, organizations involved in joint sustainability initiatives are exposed to opportunism, which discourages firms from making meaningful and intensive joint efforts [16,17,53]. The literature has called for developing effective governance mechanisms for supporting the implementation of green supply chain collaboration [16,17,50].…”
Section: Discussionmentioning
confidence: 99%
“…Trust is the basis of inter-firm cooperation; if there is no trust, a cooperative alliance is not possible or sustainable [2,44]. Lack of trust leads to uncertainty, which will cause barriers to form and inhibit the sustainability of long-term relationships [45,46]. Thus, the higher the level of trust among enterprises is, the more stable the relationship among them.…”
Section: Network Relationship Embeddedness Integrative Leadership Ementioning
confidence: 99%